Soil of the lower valley of the Dragonja river (Slovenia) - Tomaž PRUS; Nina ZUPANČIČ; Helena GRČMAN (Acta Agriculturae Slovenica)
Soil of the lower valley of the river Dragonja developed under specific soil-forming factors. Soil development in the area was influenced by alluvial sediments originating from surrounding hills, mostly of flysch sequence rocks, as a parent material, Sub-Mediterranean climate and the vicinity of the sea. Different soil classification units (Gleysol and Fluvisol) were proposed for that soil in previous researches. The aim of our study was the evaluation of morphological, chemical and mineralogical characteristics of soil, based on detailed soil description and analyses, and to define the appropriate soil classification units. Field examinations revealed that the soil had a stable blocky or subangular structure and did not express substantial hydromorphic forms. Soil pH value was ranging from 6.9 to 7.5. In most locations electroconductivity (ECe) did not exceed 2 ds/m. Base saturation was high (up to 99 %), with a majority of Ca2+ ions. Exchangeable sodium percentage (ESP) was ranging from 0.2 to 3.8 %, which is higher compared to other Slovenian soils but does not pose a risk to soil structure. Soil has silty clay loam texture with up to 66 % of silt. Prevailing minerals were quartz, calcite and muscovite/illite. No presence of swelling clay mineral montmorillonite was detected. According to Slovenian soil classification, we classified the examined soil as alluvial soil. According to WRB soil classification, the soil was classified as Cambisol.